Analysis of Toll-Like Receptors in Human Milk: Detection of Membrane-Bound and Soluble Forms. (4th December 2019) - Cattaneo, Chiara; Caramaschi, Alice; Uga, Elena; Braghin, Michela; Cosi, Gianluca; Peila, Chiara; Strozzi, Maria C.; Sabatini, Miriam; Gazzolo, Diego; Manfredi, Marcello; Cavaletto, Maria
Abstract : The bioactive and anti-inflammatory role of human milk components has been recognized; active milk components include soluble forms of Toll-like receptors (TLRs). Preterm babies are more susceptible to infections and may succumb to necrotizing enterocolitis (NEC), a gastrointestinal disease which is exacerbated by an excessive inflammatory response after TLR activation. Here, we investigated the presence of Toll-like receptors TLR1/2/4/6 in colostrum and mature milk of women who delivered before (preterm) or after (term) 37 weeks of gestational age, integrating classical immune-related techniques with proteomic LC-MS/MS analysis. We have detected immunoreactivity for TLRs mostly in preterm samples, even for TLR1 and TLR6, until now not described in human milk. We demonstrated the presence of only TLR2 in the milk fat globule membrane, while the immunoreactivity of TLR1/4/6 was ascribed to crossreaction with some interesting milk proteins sharing leucine-rich repeat domains. These results will provide new insights into the definition of the role of TLRs in intestinal immune regulation of the newborns.